Familial haematuria: when to consider genetic testing. Issue 9 (12th April 2014) - Taylor, Judy; Flinter, Frances
Abstract : Haematuria is a common finding in children. It is important to identify the underlying cause whenever possible so that appropriate follow-up is organised, particularly if the child is at risk of developing renal impairment or renal failure in later life. Until recently nephrologists relied on renal biopsy with examination under the electron microscope to make a diagnosis, but genetic testing can often provide an answer, together with additional information about the pattern of inheritance, which is also useful for other family members.